Protein disulfide isomerase-9 interacts with the lumenal region of the transmembrane endoplasmic reticulum stress sensor kinase, IRE1, to modulate the unfolded protein response in Arabidopsis - Carrillo, Rina; Iwai, Kaela; Albertson, Alena; Dang, Gabrielle; Christopher, David A. (Frontiers in Plant Science, 2024)
Environmental stressors disrupt secretory protein folding and proteostasis in the ER leading to ER stress. The unfolded protein response (UPR) senses ER stress and restores proteostasis by increasing the expression of ER resident protein folding chaperones, such as the protein disulfide isomerases (PDIs). In plants, the transmembrane ER stress sensor-kinase, IRE1, activates the UPR by unconventionally splicing the mRNA encoding the bZIP60 transcription factor, triggering UPR gene transcription. The induced PDIs catalyze disulfide-based polypeptide folding to restore the folding capacity in the ER, however the substrates with which PDIs interact are largely unknown. Here we demonstrate that the Arabidopsis PDI-M subfamily member, PDI9, modulates the UPR through interaction with IRE1. This PDI9-IRE1 interaction was largely dependent on Cys63 in the first dithiol redox active domain of PDI9, and Cys233 and Cys107 in the ER lumenal domain of IRE1A and IRE1B, respectfullyrespectively. In vitro and in vivo, PDI9 coimmunoprecipitated with IRE1A and IRE1B. Moreover, the PDI9:RFP and GFP:IRE1 fusions exhibited strong interactions as measured by Flourescence Lifetime Imaging Microscopy-Fluorescence Resonance Energy Transfer (FLIM-FRET) when coexpressed in mesophyll protoplasts. The UPR-responsive PDI9 promoter:mCherry reporter and the UPR-dependent splicing of the bZIP60 intron from the mRNA of the 35S::bZIP60-intron:GFP reporter were both significantly induced in the pdi9 mutants, indicating a derepression and hyperactivation of UPR. The inductions of both reporters were substantially attenuated in the ire1a-ire1b mutant. We propose a model in which PDI9 modulates the UPR through two competing activities: secretory protein folding and via interaction with IRE1 to maintain proteostasis in plants.